PENYULUHAN HUKUM BAGI MASYARAKAT KELURAHAN SUKA JAYA, KECAMATAN SUKARAMI, KOTA PALEMBANG: PENYELESAIAN PERKARA DI LUAR PENGADILAN SEBAGAI ALTERNATIF KEADILAN RESTORATIF - Muhammad Nur Amin; Sudarna; Derry Angling Kesuma; Rianda Riviyusnita (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This community service program was implemented to strengthen the understanding of village officials in Karangan Village regarding the risks of abuse of authority in managing Village Own-Source Revenue (PADes) and its implications for corruption offenses. Although Karangan Village possesses significant revenue potential, its administrative practices and transparency mechanisms remain inadequate. This program aims to provide legal education, technical assistance, and a risk-mapping framework to support accountable PADes management. The methods used include legal counseling, focus group discussions (FGDs), administrative observation, and assistance in preparing supporting documents. The results show increased awareness among village officials regarding asset utilization procedures, financial recording mechanisms, and the legal elements of abuse of authority under Article 3 of the Anti-Corruption Law. In addition, the program successfully identified structural vulnerabilities in PADes management that require follow-up through improved administrative practices and strengthened oversight. This community service initiative is expected to contribute to enhancing accountability and preventing corruption at the village level.